Peran Dinas Sosial Kota Surabaya Dalam Meningkatkan Kesejahteraan Penyandang Disabilitas Melalui Pelayanan Penyaluran Alat Bantu Disabilitas - Rianissaputri Rianissaputri; Dida Rahmadanik (Lembaga Pengembangan Kinerja Dosen, 2024)
The Surabaya City Government is part of the Regional Government is obliged to carry out government affairs related to basic services, including in the social sector carried out by the Social Service. The purpose of this study is to find out more about one of the services owned by the Surabaya City Social Office in the welfare of people with disabilities, namely the distribution of disability aids which are distributed free of charge and directly delivered to the homes of beneficiaries. The research method used in this study is qualitative which is carried out by literature studies based on applicable laws and regulations and interviews with Social Service employees which aim to understand more deeply about the topics in this study so that the author can present accurate data. The hope of this service is that it can provide convenience and comfort of service to the people of Surabaya in receiving assistance because it is delivered directly by officers from the Social Service.